2010
DOI: 10.1038/emboj.2010.64
|View full text |Cite
|
Sign up to set email alerts
|

Replication through an abasic DNA lesion: structural basis for adenine selectivity

Abstract: Abasic sites represent the most frequent DNA lesions in the genome that have high mutagenic potential and lead to mutations commonly found in human cancers. Although these lesions are devoid of the genetic information, adenine is most efficiently inserted when abasic sites are bypassed by DNA polymerases, a phenomenon termed A-rule. In this study, we present X-ray structures of a DNA polymerase caught while incorporating a nucleotide opposite an abasic site. We found that a functionally important tyrosine side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
73
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 77 publications
(144 reference statements)
14
73
0
3
Order By: Relevance
“…S1) have shown that purines, in particular adenosine, and to a lesser extent guanosine, are most frequently incorporated opposite the lesion. The strong preference for adenosine has been termed "A-rule" (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…S1) have shown that purines, in particular adenosine, and to a lesser extent guanosine, are most frequently incorporated opposite the lesion. The strong preference for adenosine has been termed "A-rule" (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Superior stacking as well as solvation properties of adenine have been discussed as the driving force behind adenine selection (17, 29 -31). However, previously reported structures of KlenTaq, the large fragment of Thermus aquaticus (Taq) DNA polymerase I, which is a member of the sequence family A, suggests that this enzyme follows the A-rule by applying an amino acid templating mechanism (19,20). Thereby, interaction with Tyr-671 seems to be the basis of the preference of purines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The large fragment of Thermus aquaticus (Taq) DNA polymerase (in short KlenTaq, N-terminally truncated form of Taq polymerase) was chosen as the target because this enzyme class is heavily employed and well characterized on a functional and structural level (24)(25)(26)(27)(28)(29)(30)(31). We compared two dNTP analogsnamely dT spin TP and dT dend TP (Fig.…”
mentioning
confidence: 99%
“…As the mutagenicity of protonated KP1212 is insufficiently explained by its predominant tautomeric form, we propose three other models by which the polymerase replicates across the lesion. One possibility involves the "A rule," where a polymerase replicating across a bulky damaged base or an abasic site is more likely to place an adenine in the opposing strand (33). The charged state of KP1212 may promote its ability to flip out of the helix stack, presenting the polymerase an intermediate structure reminiscent of an abasic site (Fig.…”
Section: Discussionmentioning
confidence: 99%